Pemberdayaan Masyarakat Pulau Akar Melalui Pengajaran Bahasa Inggris, Marketing dan Digital Technology Menjadi Kampung Wisata - Fasaaro Hulu; Saut Pintubipar Saragih; Sri Afridola (Pusat P2M Politeknik Negeri Batam, 2019)
Abstract - This community engagement is related to teaching English, marketing and digital technology to the people of Akar Island Batam. This activity aims to be able to communicate in English with foreign tourists, People in Island Akar are able to promote the tourism destinations and able to use digital technology and the internet as media of publication on tourism activities so that they are connected to all people all over the world. This empowerment activity was carried out in Akar Island Village, Setokok, Bulang District, Batam. Participants consisted of students, teachers and speed boat drivers. The method applied are consist of self-introduction, presentation, discussion, question and answer and practice. The results showed taht the participants got improved in English communication skills, having knowledge to conduct different and new promotionson torist objects and local products and are proficient in in using digital technology and internet to introduce to the people all activities and attractions held in Akar Island Keywords: Community service, english, tourism promotion, technology digital